The role of heuristics in the reasoning process of pre-service science teachers on the “chemical structure – acidity/basicity relationship” topic - Karakoyun, Gülen Önal; Asiltürk, Erol (Slovensko Kemijsko Drustvo, 2021)
The purpose of this research is to examine the effects of 10 heuristics proposed by Talanquer on the reasoning processes of science teacher candidates on the “chemical structure – acidity-basicity relationship” topic. In this phenomenographic research, interviews were conducted with 30 prospective teachers enrolled in the Science Education Program, Education Faculty, Firat University in the spring semester of the 2018–2019 academic year. In the first stage of the two-stage interview, the participants were asked to rank some chemical compounds according to their increasing acidity strength, while in the second stage, they were asked to rank some chemical compounds according to their increasing basicity strength. In the interviews, participants were also asked to explain in detail the reasons for their ranking. From the answers given by the participants to the questions, six different answer patterns were obtained for acidity strength, while five different answer patterns were obtained for basicity strength. It was determined that all ten heuristics affect the reasoning of the participants, and because of the effects of heuristics, students generally use shortcut strategies instead of scientific reasoning. In addition, this study revealed that although it was not included in the model proposed by Talanquer, periodic trends heuristic also affected the reasoning of the participants on the “chemical structure – acidity/basicity relationship”. © 2021 Slovensko Kemijsko Drustvo. All rights reserved.
Keywords: Acid-base; Chemistry education; Heuristic; Reasoning; Science education